Documenting a People yet to Be Named: History of a Bar Hostess - Bill Mihalopoulos (Arts, 2019)
The paper focuses on Imamura Shōhei’s History of Post-War Japan as Told by a Bar Hostess (Nippon Sengoshi—Madamu Onboro no Seikatsu), a documentary released for general viewing in 1970. The subject of the documentary was Azaka Emiko, the uninhibited middle-aged owner of the bar Onboro in the port city of Yokosuka, home to a U.S. naval base. Emiko embodied the phantasmagoric (chimimōryō) lowlifes who inhabited the nooks and crannies of Japanese cities and went about their lives without resentment or guilt, unburdened by familial responsibility and social norms that fascinated Imamura. While other intellectuals and film makers were obsessing about the status of Japanese democracy, Imamura chose to focus on people such as Emiko to identify the psychological and moral changes undergone by the Japanese people during three decades of post-war recovery and growth.